Organizational centralization in court administration: An empirical assessment - Taggart, William A. (American journal of criminal justice, 1987)
Data gathered from a national survey of court managers are used to examine the centralized versus decentralized perspectives recently developed in organizational theories of court administration. Two areas are examined in the research: administrative decision making and job formalization. Utilizing discriminant analysis, it appears that few states are dominated by a single management approach, and that in all likelihood the local norms and values influence the ways in which the courts are managed.